ปัจจัยแรงกดดัน 5 ประการที่มีผลกระทบต่อการเปิดเสรีการค้าอาเซียน (AEC) ในธุรกิจสายการบินต้นทุนต่ำ - เรืองอริยภักดิ์, เนตร์ศิริ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์การวิจัยเพื่อศึกษา 1) ปัจจัยสาเหตุของแรงกดดัน 5 ประการที่มีผลกระทบต่อการเปิดเสรีการค้าอาเซียน (AEC) ในธุรกิจสายการบินต้นทุนต่ำ และ 2) เพื่อสามารถเข้าใจผลของปัจจัย และหาแนวทางในการป้องกันความเสี่ยงที่อาจจะ เกิดขึ้น และส่งผลกระทบต่อธุรกิจโดยตรง เครื่องมือที่ใช้ในการวิจัยคือ แบบสอบถาม (questionnaire) ในการสอบถามกลุ่มตัวอย่างลูกค้าที่ใช้บริการสายการบินต้นทุนต่ำ จำนวน 200 ชุด วิเคราะห์ข้อมูลโดยใช้โปรแกรมสำเร็จรูป โดยใช้ค่าสถิติได้แก่ การแจกแจงความถี่ ค่าร้อยละ ค่าเฉลี่ย ค่าส่วนเบี่ยงเบนมาตรฐาน ค่าความเบ้ ค่าความโด่ง และการวิเคราะห์ องค์ประกอบเชิงยืนยันอันดับสอง (Secondary Order Confirmatory Factor Analysis) ผลการวิจัยพบว่า ปัจจัยสาเหตุของแรงกดดัน 5 ประการที่มีผลกระทบต่อการเปิดเสรี การค้าอาเซียน (AEC) ในธุรกิจสายการบินต้นทุนต่ำเรียงตามแรงกดดันจากมากไปน้อยได้แก่ องค์ประกอบที่ 1 อุปสรรคการกีดขวางเข้าสู่ธุรกิจสายการบินต้นทุนต่ำ ประกอบด้วย 7 ปัจจัย รองลงมาได้แก่ องค์ประกอบที่ 4 อำนาจการต่อรองของกลุ่มผู้ใช้บริการหรือลูกค้า ประกอบด้วย 5 ปัจจัย องค์ประกอบที่ 3 อำนาจต่อรองของให้บริการธุรกิจสายการบินต้นทุน ต่ำ ประกอบด้วย 4 ปัจจัย องค์ประกอบที่ 2 แรงผลักดันจากผู้ให้บริการ หรือคู่แข่งที่มีใน อุตสาหกรรม ประกอบด้วย 4 ปัจจัย และองค์ประกอบที่ 5 แรงผลักดันซึ่งเกิดจากสินค้า/ บริการอื่น ๆ ประกอบด้วย 3 ปัจจัยตามลำดับ โดยโมเดลองค์ประกอบของปัจจัยแรงกดดัน 5 ประการที่มีผลกระทบต่อการเปิดเสรีการค้าอาเซียน (AEC) ในธุรกิจสายการบินต้นทุนต่ำใน แต่ละองค์ประกอบต่างมีความเที่ยงตรงเชิงเหมือน ทั้งนี้เนื่องจากค่าความเชื่อมั่นเชิงโครงสร้างผ่านเกณฑ์มากกว่า 0.60 และค่าน้ำหนักองค์ประกอบ ซึ่งควรมีค่าตั้งแต่ 0.50 ขึ้นไป (ค่าสัมบูรณ์) แนวทางในการป้องกันความเสี่ยงที่อาจจะเกิดขึ้น ซึ่งทางธุรกิจสายการบินต้นทุน ต่ำควรหากลยุทธ์ด้านการตลาด เพื่อเสริมสร้างศักยภาพในด้านการแข่งขันก่อนที่จะมีการ เปิดเสรีการค้าอาเซียนในปี 2558 ด้วยการสร้างมูลค่าเพิ่มต่อตัวสินค้า/บริการของ ผู้ให้บริการเพื่อนำนวัตกรรมใหม่ ๆ ออกสู่ตลาด และหวังผลในระยะยาว ตลอดจนการ ดำเนินกลยุทธ์ในการบุกตลาดไปยังต่างประเทศจำต้องอาศัยความร่วมมือกันจากภาครัฐ และภาคเอกชนที่จะร่วมกันผลักดันการดำเนินการต่าง ๆ อย่างทันท่วงที และเป็นไปอย่าง ต่อเนื่อง FIVE-FORCED MODEL FACTORS AFFECTING LOW COST AIRLINES BUSINESS IN THE CONTEXT OF ASEAN ECONOMIC COMMUNITY (AEC) The research was aimed at 1) studying causal factors of five-forced model affecting low cost airlines business under ASEAN Economic Community (AEC) and 2) investigating the results of all factors and the way to prevent an incoming risk which might have a direct effect on the low cost airlines business. A questionnaire was constructed as a tool for collecting data from 200 passengers of low cost airlines. The data was statistically analyzed by frequency distribution, percentage, mean, standard deviation, skewness, kurtosis and secondary order confirmatory factor analysis. The research findings indicated that the causal factors of five-forced model affecting low cost airlines business under ASEAN Economic Community (AEC) ranking from the most to the least were the first component: threat of new entrants into the industry which comprised 7 factors then the fourth one: bargaining power of buyers which comprised 5 factors, the third one: suppliers which comprised 4 factors, the second one: intensity of the rivalry among firms within the industry which comprised 4 factors and the fifth one: threat of substitute products which comprised 3 factors. Each component of five-forced model affecting low cost airlines business under ASEAN Economic Community (AEC) had convergent validity because construct reliability was more than .60 and factor loading should be more than 0.50 (absolute). The way to prevent an incoming risk was to create marketing strategies for strengthening competitiveness before attending ASEAN Economic Community (AEC) in 2015. Value added in product for launching Product should be value added innovation result in a long run was a must. Moreover, the strategy to open up a new market in foreign countries had to be cooperated and supported by both public and private sectors promptly and continuously.